Incidence of hypotension and acute hypotensive transfusion reactions following platelet concentrate transfusions. Issue 2 (21st September 2015) - Du Pont‐Thibodeau, G.; Robitaille, N.; Gauvin, F.; Thibault, L.; Rivard, G.‐É.; Lacroix, J.; Tucci, M.
Abstract : Background and objectives: Platelet concentrates (PCs) are associated with transfusion reactions involving hypotension, particularly bradykinin‐mediated acute hypotensive transfusion reactions. This study aims to determine the incidence of hypotensive events and more specifically acute hypotensive transfusion reaction associated with PC transfusions. We also sought to ascertain whether these reactions are associated with elevated bradykinin levels. Materials and Methods: This is a prospective descriptive study of PCs administered at Sainte‐Justine Hospital over 28 months. All PCs administered during this period were screened for hypotension through review of all transfusion‐associated reaction reports (TARRs) sent to the blood bank. All residual PC bags were returned to the blood bank. TARRs associated with hypotension were reviewed by adjudicators that established the imputability of the PC transfusion to the reaction. Bradykinin levels were sampled in the first 168 PC bags returned to the blood bank. Levels were compared between PCs associated with hypotension and control PCs not associated with hypotension. Results: A total of 3672 PC bags were returned to the blood bank; 25 PCs were associated with hypotension. Adjudicators ascertained that five hypotensive events were imputable to PCs of which one was an acute hypotensive transfusion reaction (incidence: 0·03%). Bradykinin level in the latter PC was 10 pg/ml, whereas levels were 226·2 ± 1252 pg/ml in the 143 control PCs. Conclusion: Our results show a low incidence of hypotension after PC transfusion. We identified only one acute hypotensive transfusion reaction. No correlation between bradykinin level and the occurrence of acute hypotensive reactions could be observed given that only one event was identified.